A Woman with Systemic Sclerosis, Sjogren's Syndrome, and Chronic Limb Ischemic Fontaine IV Digiti II Pedis Sinistra - Gandik DP; Agus JS; Ananto W (Universitas Muhammadiyah Yogyakarta, 2021)
Systemic sclerosis is a systemic disease affecting the skin connective tissue, internal organs, and blood vessel walls, characterized by endhotel dysfunction, fibrosis, and autoantibody production. Sjogren's syndrome can appear as part of other autoimmune diseases, including systemic sclerosis (11-24%). Chronic limb ischemia is a type of peripheral arterial disease where there is blockage of the peripheral arteries due to an inflammatory or atherosclerosis process that causes arterial stenosis or thrombus formation. The Fontaine classification can assess the severity degree. A 48-year-old woman presents with stiff skin almost all over the body, especially the face, hands, feet, and back skin. She also complained of blackened and numb toes. Physical examination revealed positive Raynaud's phenomenon, Pitting scare, and deformity of both fingers. The systemic sclerosis diagnostic score was 18, which means the patient was positive for systemic sclerosis. ANA test showed strong positive Anti La / SS-B and Ro-60, which supports Sjogren's syndrome. In Fontaine classification, patients are assigned to Fontaine IV digiti II pedis sinistra. She received immunosuppressants, corticosteroids, antiplatelet agents, statin, and performed angiography. Autoimmune diseases can attack multiple organs and rarely stand on their own. Comprehensive management can provide better clinical results.